Восточнохристианская цивилизационная система и ее место во всемирно-историческом процессе - Павленко, Ю. (Социология: теория, методы, маркетинг, 2001)
The author discusses the East Christian civilization identity, specific historical features of Ukrainian-Belarus and Moscow-Russian components of the East Slavic Orthodox civilization, under the Russian Empire in particular, and analyzes the transformations of this civilization institution which took place in the 20th century. As a result, there were determined the place, role and prospects of Ukraine in the general civilization structure of modern mankind.